2021
DOI: 10.1080/09669582.2021.1928680
|View full text |Cite
|
Sign up to set email alerts
|

Decent work and tourism workers in the age of intelligent automation and digital surveillance

Abstract: Technology is shifting not only how the tourism industry is run but also the nature of work, working conditions and management control. This article examines the potential implications of technologydriven transformations on lower-paid lower-skilled tourism workers. With tourism expected to be the sector most affected by intelligent automation, greater attention needs to be given to the variegated impact on the workforce. Drawing on the concepts of surveillance capitalism, disruptive innovation and techno-solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…Physical-digital process technologies (high share of hardware components/low level of connectivity) including manufacturing equipment and novel materials, as well as energy management solutions such as hydrogen and fuel cell technologies have been identified as key Regional Innovation Policies (RIP) solutions for reducing greenhouse gas emissions and energy consumption ( Cooke and Nunes, 2021 ), or LanzaTech’s Sustainable Aviation Fuel (SAF) produced from waste gas-derived ethanol ( Kondo and Hegedus, 2020 ), and intelligent automation in tourism workplaces ( Rydzik and Kissoon, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical-digital process technologies (high share of hardware components/low level of connectivity) including manufacturing equipment and novel materials, as well as energy management solutions such as hydrogen and fuel cell technologies have been identified as key Regional Innovation Policies (RIP) solutions for reducing greenhouse gas emissions and energy consumption ( Cooke and Nunes, 2021 ), or LanzaTech’s Sustainable Aviation Fuel (SAF) produced from waste gas-derived ethanol ( Kondo and Hegedus, 2020 ), and intelligent automation in tourism workplaces ( Rydzik and Kissoon, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firms took various initiatives such as remote working capabilities and digitization; digital platforms for ease in working; document online exchange; business intelligence systems; implementation of digital management systems ( Ajmal et al, 2021 ); and automation in processes, production, and distribution channels, to make them more resistant to pandemics in the future ( Ajmal et al, 2021 ; Rydzik and Kissoon, 2021 ). Studying four hotels or lodging, Farías and Cancino (2021) found that the impact of digital innovation on core process management, both in the back office and in the front office, was determined to be critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitality sector workers have precarious employment not only because they are frontline and at risk of exposure, but they also face obsolescence due to employers quickly introducing labour saving tools and robotics (Rydzik & Kissoon, 2021). In the case of workers in the sector, compensation, working conditions, and employer support have not traditionally been generous.…”
Section: The Hospitality Industry Tests Positive: Covid-19 Perception...mentioning
confidence: 99%
“…In addition, the choice of positive words such as "smart," "connect," and "intelligent" reinforce the normalized dominant discourse of digital technology in society. In recent years, some studies have adopted a more critical approach to problematize the dominant neoliberal discourse of technology transformation in tourism (Rydzik and Kissoon 2021) and criticize the impersonal mass quantification of big data (Weaver 2021).…”
Section: Digital Technology As Disciplinary Powermentioning
confidence: 99%